Phenotypic variability of percentage of medullated fibers in Huacaya alpaca fleece - Pinares, Rubén (2019)
The objective of the study was to evaluate the phenotypic variability of the percentage of medullated fibres of Huacaya alpacas, as well as to calculate the phenotypic correlation between the average diameter of fiber (ADF) and the percentage of total medullation (PM). Fibre samples were collected from 36 Huacaya alpacas (0.4-10.4 years old males) to analyse the ADF and the PM with the projection microscope. The type of medulla of the fibres was considered as not medullated, fragmented, discontinuous, continuous and strongly medullated. A high phenotypic variability of PM between alpacas and within the samples was observed. The mean ± standard deviation of PM and ADF was 32.56 ± 18.30% and 17.58 ± 2.52 μm for non-medullated fibres; 29.29 ± 11.67% and 21.49 ± 2.39 μm for fragmented medullated fibres; 14.01 ± 10.14% and 24.04 ± 2.40 μm for discontinuous medullated fibres; 23.90 ± 13.01% and 28.04 ± 3.10 μm for continuous medullated fibres; and 0.59 ± 0.44% and 50.85 ± 9.86 μm for strongly medullated fibres, respectively. The phenotypic correlation between the PM and the ADF was 0.80, and between the PM and the percentage of continuous medullation was 0.74. In conclusion, there is a high phenotypic variability of the PM and the percentage of continuous, discontinuous and fragmented medullated fibres in the Huacaya alpaca fleece. The fine fibres have a low frequency of fragmented and discontinuous medullated fibres, while the thicker fibres have a higher frequency of discontinuous and continuous medullated fibres.